OPTIMALISASI SUPERVISI AKADEMIK KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA BERBASIS DEEP LEARNING - Arum Wardatul Husna Asyauqiya; Zahrotur Roifah; Binti Maunah; Hikmah Eva Trisnantari (STKIP Pesisir Selatan, 2025)
The quality of learning in the implementation of the Merdeka Curriculum continues to face significant challenges, particularly regarding teachers’ pedagogical competencies. National data from UKG, AKG, PMM, and Sulingjar reveal persistent gaps in pedagogical mastery, which directly affect the effectiveness of differentiated learning and the achievement of the 8 Graduate Profile Dimensions, the new national learning outcomes standard. School principals’ academic supervision is viewed as a strategic instrument to address these issues; however, previous studies have largely focused on administrative aspects, with limited attention to integrating deep learning approaches within the supervision process. This study aims to analyze the role of optimizing principals’ academic supervision in enhancing teachers’ pedagogical competencies to support the implementation of the Merdeka Curriculum based on deep learning. A literature study method was employed by reviewing books, scientific articles, educational policies, and relevant research published within the last decade. The findings show that systematic, continuous, and needs-based academic supervision can significantly improve teachers’ ability to design active and reflective learning, develop HOTS-based instructional materials, and create collaborative learning environments that support the achievement of the 8 Graduate Profile Dimensions.